2023
DOI: 10.1155/2023/4408697
|View full text |Cite
|
Sign up to set email alerts
|

Expert Opinion on the Diagnosis and Management of Male Hypogonadism in India

Abstract: Male hypogonadism (MH) is a clinical and biochemical syndrome caused by inadequate synthesis of testosterone. Untreated MH can result in long-term effects, including metabolic, musculoskeletal, mood-related, and reproductive dysfunction. Among Indian men above 40 years of age, the prevalence of MH is 20%–29%. Among men with type 2 diabetes mellitus, 20.7% are found to have hypogonadism. However, due to suboptimal patient-physician communication, MH remains heavily underdiagnosed. For patients with confirmed hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…pooled analysis of other observational studies in obese hypogonadal men with T2DM found that testosterone replacement therapy (TRT) significantly reduced-i) fasting blood glucose and HbA1c levels, ii) total cholesterol, iii) low-density lipoprotein cholesterol, iv) triglycerides, thus reducing the risk of CVD, v) levels of inflammatory markers suggesting reduction in the inflammation response, vi) increased high-density lipoprotein cholesterol levels, vii) improved systolic and diastolic blood pressure. These data were validated in a placebo-controlled study over 2 years published in January 2021 [8,9].…”
Section: Diabetic Hypogonadism and Testosterone Replacement Therapymentioning
confidence: 98%
See 3 more Smart Citations
“…pooled analysis of other observational studies in obese hypogonadal men with T2DM found that testosterone replacement therapy (TRT) significantly reduced-i) fasting blood glucose and HbA1c levels, ii) total cholesterol, iii) low-density lipoprotein cholesterol, iv) triglycerides, thus reducing the risk of CVD, v) levels of inflammatory markers suggesting reduction in the inflammation response, vi) increased high-density lipoprotein cholesterol levels, vii) improved systolic and diastolic blood pressure. These data were validated in a placebo-controlled study over 2 years published in January 2021 [8,9].…”
Section: Diabetic Hypogonadism and Testosterone Replacement Therapymentioning
confidence: 98%
“…The Endocrine Society of India (ESI) recommends TTh for men who have either less than 300 ng/dL of testosterone in the blood or symptoms of low testosterone. Measurement of serum FT and/or bioavailable testosterone is considered necessary in individuals suspected of having any disorder accompanied by increased or decreased sex hormone binding globulin (SHBG) levels [8].…”
Section: Male Hypogonadismmentioning
confidence: 99%
See 2 more Smart Citations